2010
DOI: 10.1007/s10815-010-9402-y
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetics of human male pronuclear development in a heterologous ICSI model

Abstract: Purpose To evaluate human sperm nuclear chromatin decondensation in a heterologous ICSI system using hamster ova injected with human sperm. Materials and methods Frozen hamster oocytes were injected with Triton X-100 treated sperm and fixed at different time points post ICSI. Oocytes injected with nontreated sperm served as controls. Male pronuclear decondensation was evaluated after staining with DAPI. Results Sperm cells with partially destroyed membranes and depletion of the acrosome decondense more rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Hamster oocytes are known for their high survival rate even with harsh microinjection methods and for their relatively translucent cytoplasm, which permits an easy observation of different events related to fertilization [95]. Therefore, the ICSI of human sperm into hamster oocytes has been used in the past as a model to evaluate sperm head decondensation and male pronucleus formation [96]. The ICSI of human sperm with severe male-factor infertility into hamster oocytes showed a reduced percentage of sperm head decondensation [97].…”
Section: Heterologous Icsi Testsmentioning
confidence: 99%
“…Hamster oocytes are known for their high survival rate even with harsh microinjection methods and for their relatively translucent cytoplasm, which permits an easy observation of different events related to fertilization [95]. Therefore, the ICSI of human sperm into hamster oocytes has been used in the past as a model to evaluate sperm head decondensation and male pronucleus formation [96]. The ICSI of human sperm with severe male-factor infertility into hamster oocytes showed a reduced percentage of sperm head decondensation [97].…”
Section: Heterologous Icsi Testsmentioning
confidence: 99%
“…If only one sperm is found, we must be reluctant to use it for anything but fertilization. As described above, because the cytoplasm of oocyte may induce heterogonous cell nucleus condensation, we may try to inject a sperm into an enucleated oocyte to observe sperm nucleus kinetics (Jones et al, 2010;Ogonuki et al, 2010). Recent studies demonstrated possibility of artificially replicating a single sperm genome, which could help men with very low sperm counts become fathers.…”
Section: Sperm Cell Cloningmentioning
confidence: 99%
“…Then, the membrane vesicles become progressively incorporated into the maternal pronucleus either individually or in groups. At the same time, a continuous nuclear envelope (NE) is formed around the sperm components after remodeling [6,7]. The integrity of the NE is regulated by the activity of oocyte-derived protein kinase and phosphatase interacting with lamin A, B, and C [8].…”
Section: Introductionmentioning
confidence: 99%